Evidências da eletrização de polímeros dielétricos durante a impressão 3D - Lorenzett, Ezequiel (2024)
During the fused deposition (FDM) 3D printing process, several effects are observed on the deposited polymers. These effects include phase change, extrusion, voltage gradient, friction, contact between different (polymer/substrate) and/or identical (polymer/polymer) materials and solid-liquid interfaces under temperature gradients. As a result, an accumulation of charges is observed in the printed objects, varying according to the chemical structure of the polymer and substrate and the printing parameters. In this dissertation, an extensive study was developed using a Kelvin electrode, demonstrating the spontaneous accumulation of charges in five polymers (ABS, PETG, PLA, TPU and Nylon) during and after printing. These five polymers were printed on three different substrates (glass, steel and PTFE). Then, the glass substrate was selected as a standard, and it was observed how printing parameters such as printing direction, printing speed, substrate temperature, extrusion temperature and the number of layers affect in different ways the magnitude and the distribution of generated loads. Then, dissipation measurements at rest were made to investigate the half-life of the charges. Furthermore, simple protocols were developed using common multimeters for charge monitoring. Also, methods were applied to control and mitigate charges using corona discharge and triboelectrifying the substrates with a polyethylene (PE) plate. Finally, an electret was manufactured directly on the 3D printer, indicating a potential advancement in electret technology. Thus, based on the results obtained in this dissertation, numerous advances are expected in the area of electrostatic materials and 3D printing, such as the production of parts with controlled electrical charge and the use of pre-electrified molds for application in energy collection devices and sensors.